Editorial PPP 15(2) - Santos, Larissa; Saraiva de Queiroz, Isabela; Alvarenga Filho, José Rodrigues de; Aranha de Queiroz e Melo, Maria de Fatima (Revista Pesquisas e Práticas Psicossociais, 2020)
Editorial